2005
DOI: 10.2147/nedt.1.2.145.61047
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic management of anxiety and affective lability during recovery from Guillain-Barr� syndrome: some preliminary observations

Abstract: Psychiatric symptoms in Guillain-Barré syndrome (GBS) can include anxiety and affective lability, which require treatment to improve functional outcomes. Three cases in which modest doses of selective serotonin reuptake inhibitors (SSRIs), alone or in combination with anticonvulsants, reduced symptoms of anxiety and affective lability during acute rehabilitation of GBS are presented. These agents were both more effective and better tolerated than benzodiazepines and appeared to facilitate engagement in rehabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…These results are passing with the work of Bernsen et al ( 2010 ) who found a high rate of anxiety among GBS patients in early disease stages and attribute this to ICU admission, fear of need of assisted ventilation and haziness in the expectation about the future prognosis, but on the contrary, they found positive correlation with rapidity of disabilities possibly due to non-exclusion of those needed assisted ventilation who may have more rapid disease course. Brousseau et al ( 2005 ) went beyond these results, and they found higher rate of anxiety, depressive symptoms, and brief reactive psychosis in GBS patients than that in ICU-admitted patients for other indications with near degree of disability and supposed that psychiatric symptoms are parts of the clinical manifestations of GBS.…”
Section: Discussionmentioning
confidence: 98%
“…These results are passing with the work of Bernsen et al ( 2010 ) who found a high rate of anxiety among GBS patients in early disease stages and attribute this to ICU admission, fear of need of assisted ventilation and haziness in the expectation about the future prognosis, but on the contrary, they found positive correlation with rapidity of disabilities possibly due to non-exclusion of those needed assisted ventilation who may have more rapid disease course. Brousseau et al ( 2005 ) went beyond these results, and they found higher rate of anxiety, depressive symptoms, and brief reactive psychosis in GBS patients than that in ICU-admitted patients for other indications with near degree of disability and supposed that psychiatric symptoms are parts of the clinical manifestations of GBS.…”
Section: Discussionmentioning
confidence: 98%
“…A review of the recent literature suggests that GBS patients, and close relatives of GBS patients, are indeed at increased risk of psychiatric symptoms. Table 1 includes six case studies reporting anxiety, lethargy and sleep disturbance at the onset of physical disability, as well as residual psychiatric symptoms at one to four weeks after GBS onset [12][13][14][15]. Two case studies reported that psychiatric symptoms preceded onset of physical disability, including stress, depression, anxiety and amnesia [16,17].…”
Section: Reviewmentioning
confidence: 99%
“…Fear and anxiety associated with the suddenness in onset and severity of physical disability during the acute phase of GBS may impact on the psychological status of the patient and, although most patients experience improvement in physical symptoms, many experience longterm severe residual anxiety, depression, and fatigue [10,28]. The prevalence of anxiety and depression in GBS patients is higher in comparison to other patients admitted to ICU for other conditions [12]. One hypothesis to explain residual psychiatric sequelae is dysfunction of the HPA axis resulting from a prolonged stress response to the antecedent infection that triggered the autoimmune neuropathy [40].…”
Section: A Multidisciplinary Team Approach For the Management Of Gbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strength and sensory deficits tend to depict the clinical profile when assessing patients with GBS and CIDP. A substantial number of patients with GBS or CIDP were observed to experience depressive episodes and increasing attention has been afforded to the burden of depressive syndromes and their influence on a patient's quality of life ( 41 43 ). In a population-based cohort study on the risk of psychiatric disorders in GBS, the hazard ratio (HR) of 4,548 GBS patients with regards to the development of psychosis was 4.320 (adjusted HR, 95% confidence interval (CI): 3.852–4.842, p < 0.001), and in depressive disorder was 4.834 ( p < 0.001), in comparison to a control group ( 44 ).…”
Section: Prevalence and Profilementioning
confidence: 99%